THE NOVEL MITOCHONDRIAL FISSION PROTEINS, MID49 AND MID51: NEW THERAPEUTIC TARGETS FOR CARDIOPROTECTION. (21st November 2014) - Elder, JM; Samangouei, P; Burke, N; Hall, AR; Osellame, LD; Ryan, MT; Hausenloy, DJ
Abstract : Rationale: Ischaemic heart disease is the leading cause of death and disability worldwide. Modulating mitochondrial morphology by inhibiting mitochondrial fission during acute ischaemia-reperfusion injury (IRI) has been reported to protect the heart against cell death. Here, we investigate the newly discovered mitochondrial fission proteins, MiD49 and MiD51, as novel targets for cardioprotection. Methods and Results: Genetic ablation of both MiD49 and MiD51 in HL-1 cardiac cell using shRNAs had the following effects: A significant increase in the proportion of cells expressing predominantly elongated mitochondria (81.5±2.9% MiD49+MiD51 knockdown vs. 49.4±4.9% vector control: n=120 cells/group; P<0.05) A delay in time taken to induce mitochondrial permeability transition pore (MPTP) opening (485±61 seconds MiD49+MiD51 knockdown vs. 233±20 seconds vector control: n=120 cells/group; P<0.05) Less cell death following simulated IRI (27.9±3.0% MiD49+MiD51 knockdown vs. 56.7±2.4% vector control: n=300 cells/group; P<0.05). Ablation of MiD49 or MiD51 individually had no beneficial effects. Unexpectedly, the over-expression of either MiD49 or MiD51 also had beneficial effects: The formation of abnormally elongated (hyperfused) mitochondria with a peri-nuclear distribution; It delayed the induction of MPTP opening; and It reduced cell death following simulated IRI. The explanation for this apparent beneficial effect with MiD49 or MiD51 over-expression, may be due to Drp1 sequestration to mitochondria, leading to unopposed abnormal mitochondrial elongation (hyperfusion). Conclusions: Here, we show that combined knockdown of the newly discovered mitochondrial fission proteins, MiD49 and MiD51, induced mitochondrial elongation, delayed MPTP opening, and protected cells against simulated acute IRI, positioning these proteins as novel targets for cardioprotection.